Penerapan Pembelajaran Kooperatif Dalam Perkuliahan Konseling Kelompok Pada Mahasiswa Bimbingan Konseling Fakultas Dakwah Dan Ilmu Komunikasi UIN Raden Intan Lampung - Muhammad Saifuddin; Sri Ilham Nasution (Cetta: Jurnal Ilmu Pendidikan, 2020)
The results of Class Counseling student learning outcomes VI semester Counseling Guidance Department, Faculty of Da'wah and Communication Studies, UIN Raden Intan Lampung in the previous year showed the low ability of students, especially in the subject of group dynamics and stages of group counseling. This condition is caused by poor understanding and skills regarding group counseling, new material, and lecture models or approaches used by lecturers are not optimal. Therefore, the problem solved through this research is "Can the application of the Cooperative Learning Model (STAD) improve the quality of Group Counseling lectures?". Class interventions in this study were carried out in two cycles. Data collection is done by testing and observation techniques. Benchmark of success of the action is if the average formative test score of the student is more than or equal to 70 (B) and the classical learning completion is at least 75%, the value of student learning activities and the lecturer perfomance score is at least 70 or B. Average acquisition Student formative test scores after the application of the cooperative learning model (STAD) in the first cycle were 71.21 and the classical learning completion was 63.16%. In cycle II student learning outcomes increased by 4.79 points to 76 and classical learning completion increased by 21.05% to 84.21%. Student learning activities in the first cycle reached a value of 77.5 (B) and in the second cycle increased by 6.25 points to 83.75 (A). The lecturer performance, in cycle I obtained a value of 78.75 (B) and in the second cycle increased to 83.12 (A). Thus, it can be concluded that through the cooperative learning model (STAD), the quality of Group Counseling lectures at the Guidance Counseling Department can be improved. It is therefore recommended, lecturers who are able to take Group Counseling courses, especially on group dynamics material and stages of group counseling use cooperative learning models (STAD) as an alternative.